O Interc??mbio de Energia como Mecanismo de Inser????o Regional do Brasil no Cone Sul - Queiroz, Fernanda Hellena de Lima (2015)
This dissertation presents regional economic co-operation as a facilitator for the development of energy governance strategies, focusing Brazil???s regional insertion in the continent???s Southern cone. The main goal of this Masters level dissertation is to analyse the practices made by Nordic???s model of electricity production & commercialisation (Nord Pool), establishing a paradigm between Brazil???s model in force and the interaction possibilities with Brazil???s neighbouring countries. The feasible strategies for the creation of optimal environments, the influence of economic co-operation in the negotiations carried on by South American countries and the guidelines of energy governance will also be analysed for the growth at the electricity supply levels (energy security), regional development and social welfare.